Uncertainty analysis and risk identification of the gravity dam stability using fuzzy set theory - Fakhreddin Moradi Kia; Hamid Ghafouri; Mohammad Mehdi Riyahi (Journal of Hydraulic Structures, 2022)
This paper introduces a methodology in which the fuzzy theory has been used along with numerical modeling of a gravity dam. For this purpose, using the fuzzy set theory method, the Folsom gravity dam in the USA, which is modeled in ANSYS and CADAM softwares, its uncertainties are analyzed. It is shown that with 10% variation in the input variables, about -92.31 to +78.6% uncertainty is created in the heel stability of the dam. Another part of this paper focuses on sensitivity analysis based on inputs and shows how inputs affect the outputs. From this sensitivity analysis can be proven that the output parameters have a monotonic behavior and the fuzzy outputs can be extracted without the need for an optimization algorithm. This paper also presents a new concept of risk identification derived from the fuzzy set theory to increase the stability awareness of the Folsom gravity dam. The minimum amount of uncertainty that leads to the risk area is 0.02%, which is related to S1 in loading condition 2.